COLLABORATION IN HA JJ RESEARCH TO ENSURE EFFICIENCY IN HA JJ MANAGEMENT - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 8 April 2016 “ I was quite thrilled with the dedication and support from Malaysia and Universiti Sains Malaysia (USM) in implementing a programme such as this and I am confident that if it could be done well, Malaysia would lead in this field of hajj research,” said Senior Consultant on Infectious Diseases and Chairperson, Research Department, Hospital Prince Mohamed bin Abdul Aziz, Professor Dr. Ziad A. Memish.